The Applying of Hypothetical Learning Trajectory (HLT) on Comparison Material Using Nisab Zakat Theory toward The Student's Learning outcomes - Putra, Yudi Yunika; Saputra, Adi (Al-Jabar: Jurnal Pendidikan Matematika, 2018)
The problems in learning mathematics, especially comparative material, have not combined with religious theory in the learning process. The merging of Knowledge , especially mathematics with the knowledge  of religion is very important, because in addition to getting mathematics, the student will directly learn about the knowledge  of religion. The comparative learning using the Nisab Zakat theory will encourage  to bring out reasoning abilities and students think creatively, and innovative in solving the problem. The aims of the research is to find out how the influence of applying of HLT toward the student's reasoning on the third semester of Education of elementary teacher department  in STKIP Muhammadiyah Bangka Belitung. The research method of this research is quasi-experimental design. Data collection techniques are tests with hypothesis testing using t-test statistical formula. The average value of pretest before HLT applied in learning is 64.7 with a minimum value of 49, and a maximum value of 75.8. While the value on the post-test after being applied to HLT obtained an average value of 86.4 with the minimum value of 67 and the maximum value of 100. Then with this it can be concluded that there is a positive effect of the application of HLT (Hypothetical Learning Trajectory) comparison material using the Nisab zakat theory on results Student learning mathematics comparison material.